The Role of the British Government in the Spread of Scientific Management and Fordism in the Interwar Years - Lewchuk, Wayne (The Journal of Economic History, 1984)
The slowness with which British firms adopted Scientific Management and Fordism has often been noted.The paper argues that in Britain, management had difficulty controlling labor effort norms after 1870. The state intervened to resolve the issue and in the process became a major proponent of industrial democracy. It is argued that the early interest in industrial democracy retarded the adoption of American methods that assumed a greater degree of managerial control over factory organization.